SEXUALITY IN PREGNANCY - Cruz, Víctor (2015)
A survey on sexuality during pregnancy 500 postpartum women who had a recent pregnancy and childbirth complications was performed. These patients were treated at the services of Obstetrics Hospital Edgardo Rebagliati Martins National LPSs. Most were between 27 and 35 years old, secondary or higher education and was married. The frequency of intercourse dropped from three or more times a week (53%) before pregnancy once a week to every two weeks in the middle of the pregnant women in the third trimester. 24 percent had no intercourse in the last quarter. Satisfaction also fell in the course of pregnancy, while increased discomfort. 72 percent reported some discomfort during intercourse, mainly in the third quarter (37%). The side position during intercourse was the most used after the sixth month of gestation. The attitude of these variables husband was understanding.